Coach strategies for fostering positive youth development through sports - Erdilanita, Ulma; Ma'mun, Amung; Berliana, Berliana (Jurnal Ilmu Keolahragaan, 2025)
Background. Adolescence is a crucial stage of development that significantly influences future well-being. Sport participation has been shown to support positive youth development by enhancing physical health, life skills, and self-esteem. Coaches play a vital role in creating supportive sport environments that foster holistic growth. Objectives. The purpose of this research was to identify and review strategies used by coaches to encourage positive youth development through sport. Methods. The method used is a literature review. Together with colleagues, articles were sorted through the Taylor & Francis database. A review was carried out on articles from 2020 to 2024 using the PRISMA flowchart for selection and extraction. Data search was carried out using the keywords "Coach" AND "Positive Youth Development" and "Fostering" AND "Positive Youth Development". Found 956 articles through Taylor & Francis, then analyzed based on title and abstract to form 15 articles. Of the 15 articles, 7 articles were excluded because they only described the positive impact of sport on the positive development of youth but did not focus on the strategies implemented by coaches, so there were 8 articles that met the criteria. Results. The results of the review of 8 articles show the importance of constructive feedback from coaches, community empowerment and effective sports interventions, coach-player collaboration and decision making, maintaining enjoyment in sports, autonomy support to increase motivation in adolescents. Conclusion. These findings may also contribute to efforts to create more inclusive, supportive and empowering sports environments for youth from diverse backgrounds.